2010
DOI: 10.1111/j.1365-3032.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

The adipokinetic hormones of Heteroptera: a comparative study

Abstract: The adipokinetic hormones (AKHs) from 15 species of heteropteran Hemiptera (encompassing eight families, six superfamilies and three infraorders) have been isolated and structurally identified using liquid chromatography coupled with mass spectrometry. None of the structures are novel and all are octapeptides. These peptide sequence data are used, together with the previously available AKH sequence data on Heteroptera, to create a larger dataset for comparative analyses. This results, in total, in AKH sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 57 publications
(76 reference statements)
0
33
0
Order By: Relevance
“…Other vertebrate candidates whose function can be compared with AKHs are adiponectin (Tsao et al 2002) and resistin (Holcomb et al 2000), peptide hormones discovered in the last decade from vertebrate adipose tissue, which modulate a number of metabolic processes, including glucose regulation and fatty acid catabolism (Diez and Iglesias 2003;Nogueiras et al 2010). The primary structure of adiponectin (MW=25-35 kDa; Diez and Iglesias 2003) and resistin (MW=12.5 kDa; McTernan et al 2006) differs substantially from that of members of the AKH family (Kodrík et al 2010). Moreover, there is no information available on adiponectin-like and resistin-like peptides or their activity in insects.…”
Section: Introductionmentioning
confidence: 99%
“…Other vertebrate candidates whose function can be compared with AKHs are adiponectin (Tsao et al 2002) and resistin (Holcomb et al 2000), peptide hormones discovered in the last decade from vertebrate adipose tissue, which modulate a number of metabolic processes, including glucose regulation and fatty acid catabolism (Diez and Iglesias 2003;Nogueiras et al 2010). The primary structure of adiponectin (MW=25-35 kDa; Diez and Iglesias 2003) and resistin (MW=12.5 kDa; McTernan et al 2006) differs substantially from that of members of the AKH family (Kodrík et al 2010). Moreover, there is no information available on adiponectin-like and resistin-like peptides or their activity in insects.…”
Section: Introductionmentioning
confidence: 99%
“…The assigned primary sequence was confirmed by co-elution of the synthetic peptide with the natural compound in LC-MS and RP-HPLC, in addition, the synthetic peptide exhibited the same mass spectral characteristics as the native peptide from the CC. The assigned octapeptide has the structure pGluVal-Asn-Phe-Ser-Pro-Ser-Trp amide, is denoted Anaim-AKH and was previously shown to occur in the CC of A. imperator (Gäde et al, 1994) and more recently has also been found in other Odonata (Gäde and Marco, 2005;Gäde et al, 2011), as well as in water bugs of the families Notonectidae Kodrik et al, 2010), Naucoridae (Gäde et al, 2007) and Aphelocheiridae (Marco et al, 2011). It differs from Peram-CAH-I only at position 7 (Ser 7 in Anaim-AKH versus Asn 7 in Peram-CAH-I) ( Table 3).…”
Section: Structural Information and Its Interpretation For The Positimentioning
confidence: 99%
“…Preparation of extracts, purification and structure elucidation via liquid chromatography-mass spectrometry (LC-MS) and confirmation of structure Methanolic extracts were prepared from the dissected CCs as described earlier (Gäde et al, 1984). The dried material was either taken up in water to perform heterologous bioassays, or in 15% acetonitrile plus 0.1% trifluoroacetic acid (TFA) for reversed-phase high performance liquid chromatography (RP-HPLC) according to Gäde (1985), or were prepared for LC-MS. For the extract of Afronurus spp., an LCQ mass spectrometer from Thermo Electron (San Jose, USA) was used as outlined previously (Gäde et al, 2003); for the other mayfly extracts, a LTQ XL instrument of Thermo Fischer was used as described previously (Kodrik et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…An aliquot, representing about 1 gland equivalent, was then fractionated and analyzed using a Jupiter RP Proteo column (150 mm × 1 mm i.d. ; Phenomenex Inc., Torrance, USA) coupled directly to a linear quadrupole ion trap mass spectrometer (LTQ XL; Thermo Fisher, San Jose, USA) equipped with a HESI II electrospray ionization source operated at 3.5 kV and scanning mass range 400-1400 Da as outlined previously [22]. The same conditions (HPLC Jupiter Proteo column and HESI II ion source) were also used to estimate the elemental composition of the detected MH + AKH peptide ions by high resolution mass spectrometry on a QExactive Plus Orbitrap mass spectrometer (Thermo Fisher, Bremen, Germany) operated at 70,000 resolution (FWHM) with internal calibration using the background ion of diisooctyl phthalate at m/z 391.28429.…”
Section: Liquid Chromatography Coupled To Mass Spectrometry (Lc-ms)mentioning
confidence: 99%